Yemeni Diaspora in the Novels of Mohammed Al-Aswad: Hybrid Identities, Memory, and Belonging - Ahmed Mocbil (Sociedad & Tecnología)
This study examines the literary representations of the Yemeni diaspora's negotiation of hybrid cultural identities, as depicted in the novels of Mohammed al-Aswad. Drawing on the theoretical frameworks of Homi Bhabha's (1994) "third space" and Stuart Hall's (1990) conceptualization of diaspora as a "production," the analysis explores how the Yemeni diaspora navigates transnational spaces and the politics of belonging. The study also investigates the role of memory and nostalgia in shaping the diasporic consciousness, engaging with Hall's (1990) and Avtar Brah's (1996) theoretical perspectives. Through a close textual analysis of five of al-Aswad's acclaimed novels, the research contributes to a deeper understanding of the unique cultural, historical, and political factors that shape the Yemeni diaspora's experiences of identity formation and belonging. The findings demonstrate the complex ways in which the Yemeni diaspora constructs, performs, and contests hybrid identities within the "diaspora space" (Brah, 1996).